A new microhylid frog species of the genus Platypelis from phytotelmata of Pandanus screw pines in the Sorata massif, northeastern Madagascar - Rakotoarison, Andolalao; Petzold, Alice; Scherz, Mark D.; Crottini, Angelica; Köhler, Jörn; Hawlitschek, Oliver; Ratsovaina, Fanomezana M.; Glaw, Frank; Vences, Miguel (Zootaxa, 2025)
We revise the molecular variation and taxonomy of an assemblage of lineages of endemic Malagasy cophyline microhylid frogs, previously considered to be allied to Platypelis tetra. Based on DNA sequences obtained from the P. tetra holotype via a museomics approach and further complementary DNA sequences of other specimens obtained by Sanger sequencing, we genetically characterize the species and reveal at least two additional genetic lineages associated to it. These differ by uncorrected pairwise distances of 4.4–5.0% in a fragment of the mitochondrial 16S rRNA gene and require taxonomic revision in future work. A further lineage previously assigned to P. tetra differs by 16S distances of 7.1–7.8% and occupies an isolated phylogenetic position. We here formally name and describe this new species from the Sorata Massif as Platypelis efatra sp. nov. and thereby increase the number of nominal Platypelis species to 18. We provide a description of its skeleton based on a micro-computed tomography scan of a paratype, which is the first detailed osteological description of a Platypelis species, and identify some possibly diagnostic osteological differences compared to P. tetra. We furthermore provide an updated advertisement call description for P. tetra from its type locality and briefly discuss the status of a divergent population from Ambodivoangy that we tentatively assign to P. tetra pending future study.